Exploring Inputs And Outcomes Of E-Learning Implementation - Jozua Ferjanus Palandi (IC-ITECHS, 2020)
E-learning is a part of the advancement of information and communication technology, which is an important element in the world of education. To avoid the failure of e-learning implementation for achieving a goal, beforehand, it is necessary to know the factors that affect the process. This study used a literature review to explore appropriate inputs and outcomes for the tertiary leve of educationl. This study indicated four factors that need to be considered for implementing e-learning in higher education, such as student characteristics, lecturer characteristics, technology characteristics, and design and content characteristics. The emphasis of this topic was the characteristics of each factor in e-learning, especially in the higher education institutions. Besides, this study also reviewed several frameworks and their components related to e-learning. The successful implementation of e-learning depends on good development designs and implementation procedures of e-learning. In the end of this research, it constructed considerations that can be used for e-Learning implementation, specifically in the college level.